Saudi Arabia and Indonesian Networks: On Islamic and Muslim Scholars - Al Qurtuby, Sumanto (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2021)
This article investigates Indonesian scholars educated in Saudi Arabia, both historically and in contemporary contexts, including those who pursued non-Islamic fields and developed academic careers within Saudi higher education. The study adopts a qualitative approach grounded in historical inquiry and literature-based research. It traces long-standing traditions of scholarly mobility from the Malay–Indonesian world to the Saudi Arabia, particularly the Hijaz, while also mapping the educational networks, career trajectories, and religious orientations of alumni of Saudi Islamic educational institutions. The findings demonstrate that Indonesian Saudi-trained scholars are far from homogeneous. They display considerable diversity in religious orientations, social networks, academic backgrounds, and intellectual commitments. While some are associated with ultra-conservative and militant tendencies, others exhibit more moderate and progressive dispositions. The study further shows that, although the number of Indonesian scholars residing in Saudi Arabia has declined sharply over the past four decades, a new development has emerged: a small but growing group of Indonesian Muslim intellectuals trained in non-Islamic disciplines has begun to secure teaching positions at several Saudi universities. This article contributes to Indonesian Islamic historiography and transnational Islamic studies by foregrounding the plurality and complexity of Saudi-educated Indonesian scholars. It also offers a refined mapping of shifting roles played by these figures in shaping Indonesian Islam, contemporary socio-religious dynamics, and educational developments.